Comparison of self‐collected meatal swabs with urine specimens for the diagnosis ofChlamydia trachomatisandNeisseria gonorrhoeaein men. Issue 2 (February 2017) - Berry, Lisa; Stanley, Belinda
Abstract : Purpose. : Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) are common bacterial causes of sexually transmitted infections. Self‐taken meatal swabs are a possible alternative to urine samples in testing for infection; however, the data surrounding their use are limited. Methodology. : We carried out a prospective service review in a large sexual health clinic comparing urine samples and self‐taken meatal swabs in men presenting for sexual transmissible infection screening for CT and GC with the BD Viper XTR system. Results. : We found an overall prevalence of 10.5 % for CT infections and 4.2 % for GC infections in our patient population. Meatal swab testing had a sensitivity and specificity of 91 and 99 % with an negative predictive value (NPV) of 99 % and a positive predictive value (PPV) of 96 % for CT testing compared to a sensitivity and specificity of 100 and 99 % with an NPV of 100 % and a PPV of 98 % for urine samples. The sensitivity and specificity of meatal swabs was 100 and 99 %, respectively, for GC detection with an NPV of 100 % and PPV of 89 % compared to urine which had 93 % sensitivity and 99 % specificity with an NPV and PPV of 99 and 93 %, respectively. Conclusions. : Meatal samples were not inferior to urine samples for the detection of CT and GC. Male urethral meatal self‐sampling offers an alternative sample type when compared to male urine specimens.